Experimental investigation of particulate matter structures under partially premixed combustion in a compression ignition engine. (1st January 2020) - Chen, Hanyu; Wang, Minfei; Wang, Xi; Li, Deqiang; Pan, Zhixiang; Bae, Choongsik
Highlights: Particulate matters from diesel and DLH are studied in PPCI. Compared with diesel, DLH has fewer particles and smaller particle size. The primary carbon particle structure of DLH is more ordered. Contrary to diesel, the average diameter of DLH decreases with load increases. Abstract: A study on particulate matter (PM) of a compression ignition engine under partial premixed combustion has been performed. Particularly, the microscopic analyses (SEM and TEM) of several samples at the exhaust were carried out to describe the morphology and ordering degree of particles produced by the combustion of diesel and 15% diesel blended with 85% light hydrocarbon (named DLH). Characterization parameters such as fractal dimension, fringe separation distance, fringe length and fringe tortuosity were analyzed to further study the particle structure. Besides, the particle size distributions at medium and high load were compared. The results demonstrated that the particle size distribution presents as quasi-monodisperse and the average diameter of DLH is smaller than that of diesel. The diesel particles move to a larger size range at higher load, while DLH particles show an obvious shift to smaller particles at higher load, which is related to the competition between surface growth and oxidation rates.